Strangers in a strange land no longer: using APIs to create a seamless user experience - Betz, Sonya (My University, 2014)
Betz discusses how her library embarked on a dramatic re-visioning of their online space. Instead of sending students out into the scary (and not so user-friendly) world of disparate vendor user interfaces, they began using commercial and home-grown APIs to keep students wthe library in a fully integrated and customized web environment. They developed a fully-featured iOS app that integrates APIs and web services from Ebsco Discovery Service, Sirsi Symphony, and the Atlas Ares eReserves software. She talks about the big benefits of keeping Library users "in-house."
Presented on April 8, 2014 at Computers in Libraries held at the Washington Hilton in Washington, DC.
Keywords: user experience; libraries; mobile applications; responsive web design; APIs